ПРОКУРАТУРА ХОДИМЛАРИНИНГ МАСОФАВИЙ МАЛАКАСИНИ ОШИРИШДА ТЬЮТОРЛИК ФАОЛИЯТИНИ ТАШКИЛ ЭТИШ - Ибраймов, А.Е. (SCIENCE and SOCIETY, 2021)
The article highlights the features and requirements for the organization of the tutor’s work in the process of professional development in the prosecutor’s office in remote and mixed forms.